A Comparative Study Of Some Defensive Skills In Handball For Forth Year College Of Physical Education Students In Both Salah AlDin And Koia Universities - Qassim, Jmeel; Dilshad, Hawdeer (Journal of Physical Education, 2009)
The aim of the research is to identify the level of performing some defense skills in handball by the students of the colleges of physical education in the universities of Salah Aldin and Koia. In addition to that the research aimed at identifying the differences in the level of performing some defense skills in handball by the students of the colleges of physical education in the universities of Salah Aldin and Koia. The researchers used the descriptive method by comparing. The subjects of the study were (10) forth – year students taken from each college of physical education in both the university of Sala Aldin and the university of Koia. The total number of the subjects is (20) students from both colleges. The defensive skills were determined by the researchers and were presented to experts in handball. Four defensive skills were selected for having the highest percentage then the researchers selected the important of these skills and accordingly made the pilot study and pretests. The tests were applied on the members of the subjects. The data of the tests were collected using SPSS for data analyses and other statistical operations like (percentage, median, mean, standard deviation, t tests etc). Then the results were placed in tables and discussed according to scientific references. The results showed that there are differences in the performance of some defensive skills in forth year college students of both colleges in favor of Salah Aldin University. In the light of these results the researchers recommended paying attention to developing defense skills in the students of Koia University as well as the necessity of paying attention to sport facilities like indoor courts, athletic equipments in the college of physical education /University of Koia